After Hitler : recivilizing Germans, 1945-1995 - Jarausch, Konrad H (Oxford University Press, 2006)
This book deals with the transformation of Germany after the Second World War and the Holocaust into a Western, democratic, and therefore civilized country. It proceeds in three stages, beginning with the Allied post-war policies of demilitarization, denazification, and decartelization. In the second part, it concentrates on the Westernization, inner democratization and generational rebellion of the 1960s, concluding with a section on the repudiation of Communism, the return to normalcy, and the issue of immigration during the 1990s.